A critical examination of non-Native practice of Native American religion - Goar, Allison Marie, author; Vernon, Irene S., advisor; Black, Ray, committee member; Vigil, Patricia, committee member (Colorado State University. Libraries, 2016)
This qualitative study examines the experiences and perceptions of non-Native American people who practice Native American religion. Semi-structured interviews with ten participants, all of whom identify as Caucasian or White, reveal a series of strategies to avoid or dismiss critiques of cultural appropriation. These strategies include, but are not limited to: neoliberal values, the practice of spiritual materialism, denial of spiritual agency, and racial stereotyping.